Evaluating a continuing medical education program: New World Kirkpatrick Model Approach - Shih-Chieh Liao; Shih-Yun Hsu (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
The New World Kirkpatrick (NWKM) four-level model is a new vision of the Kirkpatrick Model. NWKM adds new elements to recognize the complication of the educational program background and to evaluate the effectiveness of continuing education. This study used data collected from subjects, distributed to 393 participants enrolled in an acupuncture training program in Taiwan from 2010 to 2017, to explore the implication of NWKM for evaluating the effectiveness of continuing medical education and to discuss the connection and transition among the four levels of NWKM. Exploratory factor analysis was used to address that the items in the survey were grouped in different categories and mapped onto the four levels of the NWKM. Path analysis was used to describe the directed dependencies among the levels of NWKM. The results of path analysis showed that a positive relationship exists between any two levels, but direct effects can be observed only between two consecutive levels. It means that L4 outcomes can only be directly predicted by L3, but neither L1 nor L2. L4 is the ultimate outcome of evaluating the effectiveness of continuing education, but it is hard to achieve. This research concluded that L3 is the key to evaluate continuing medical education.
Keywords: I19; I21; 330; Continuing medical education; new world Kirkpatrick model; curriculum evaluation; acupuncture; exploratory factor analysis